Ultrasonography for non-displaced and mini-displaced humeral lateral condyle fractures in children - 张敬东 陈华 (Chinese journal of traumatology, 2008)
Objective： To evaluate the value of ultrasonography in non-isplaced and mini-displaced humeral lateral condyle fractures in children. Methods： Nine children aged 2-9 years with non-displaced or mini-displaced humeral lateral condyle fractures were examined by high-resolution ultrasonography. The fracture line through the joint surface was visualized by ultrasonography in 6 case, in which closed reduction and percutaneous pinning was performed on 3 patients and other 3 patients did not receive the treatment because of patients＇ or their parents＇refusal. In the remaining 3 children, ultra- sonography did not reveal the cartilaginous trochle involvement at the joint surface and conservative treatment was adopted. Results： The average follow-up period was 8 months. The sonographic findings were confirmed by magnetic resonance imaging in one child who received conservative treat-ment and another child who received percutaneous pinning. The elbow function and fracture healing were good in cases received closed reduction and percutaneous pinning. Among the three cases who refused to receive closed reduction and internal fixation, re-displacement occurred in 1 case and delayed union in 1 case. All three cases receiving conservative treatment had good results both in elbow function and fracture healing. Conclusion： High-resolution ultrasonography enable to reveal non-displaced and mini-displaced humeral lateral condyle fractures as well as to ascertain whether the cartilaginous trochlea humeri was involved. For these cases, arthrography or magnetic resonance imaging is unnecessary.